(untitled) (LEGAL DIALOGICA, 2025)
Online fraud has emerged as a critical challenge amid the rapid development of information technology, which is not matched by the improvement of digital literacy. This study aims to examine the efforts undertaken to combat online fraud and to identify the contributing factors behind its occurrence. Data were obtained through a qualitative approach involving individuals with relevant experiences. The findings indicate that law enforcement officers have implemented various measures, including public education, institutional collaboration, complaint service provision, and capacity building in the field of cyber operations. However, the enforcement process still encounters several obstacles, such as restricted access to banking data, low levels of public participation in reporting, and insufficient monitoring of digital transactions. Factors contributing to online fraud include limited digital literacy, easy access to technology, weak identity verification systems, and economic motives of offenders. The research also reveals that preventive efforts have not been evenly or systematically implemented, and not all officers possess sufficient technical capacity for handling cyber cases. This study emphasizes the need for enhanced inter-agency cooperation, the development of early detection systems, and continuous public education as integral components of a comprehensive prevention strategy. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis upaya hukum kepolisian Resort Kota Besar Kota Makassar dalam penanggulangan tindak pidana penipuan online serta mengidentifikasi faktor-faktor yang menyebabkan terjadinya tindak pidana tersebut. Metode yang digunakan adalah penelitian hukum empiris dengan pendekatan kualitatif, melalui wawancara kepada aparat kepolisian, korban, pelaku, serta masyarakat dan tokoh agama.Hasil penelitian menunjukkan bahwa pihak kepolisian telah melakukan berbagai upaya dalam menanggulangi tindak pidana penipuan online, antara lain melalui edukasi masyarakat, kerja sama dengan lembaga terkait seperti OJK dan perbankan, penyediaan saluran pengaduan, serta peningkatan kapasitas sumber daya manusia (SDM) di bidang siber. Namun, upaya penegakan hukum masih menemui berbagai hambatan, seperti kerahasiaan data perbankan dan kurangnya literasi digital di kalangan masyarakat. Faktor-faktor yang mendukung terjadinya penipuan online di Kota Makassar meliputi kemudahan akses teknologi, rendahnya literasi digital, lemahnya sistem verifikasi identitas digital, serta motif ekonomi pelaku. Penegakan hukum oleh kepolisian dinilai masih memerlukan penguatan dari sisi regulasi, sarana-prasarana, serta sinergi antarlembaga guna menekan angka kejahatan siber yang terus meningkat.Penelitian ini diharapkan dapat memberikan kontribusi dalam perumusan strategi penanggulangan penipuan online secara lebih efektif, baik dalam aspek preventif, represif, maupun edukatif.